Strategic business development and client prospecting in the third-party apartment management industry - Read, Dustin C.; Goss, Rosemary Carruci; Hopkins, Erin (International Journal of Strategic Property Management, 2017)
Intensifying competition and increasing market demands are forcing many third-party apartment management firms to re-evaluate their approach to business development and client prospecting. In some instances, these companies are becoming more selective about both the assignments they take on and the property owners with whom they work. Careful consideration is frequently given to a number of factors to determine if new business opportunities are a good strategic fit. This paper examines how sophisticated fee management firms make such determinations by examining the perspectives of executives representing 25 of the largest multifamily operators in the United States. The results indicate heavy reliance on relational approaches to business development, limited long-range planning, and informal channels of communication often encourage fee managers to pursue new business in an ad hoc manner despite market conditions favouring more systematic behaviour. A series of best practices are put forth to address these concerns.